Educational Reforms Set Professional Boundaries: The Spanish Audit Function, 1850–1988. (19th February 2013) - Carrera, Nieves; Carmona, Salvador
Abstract : Research on the accounting profession considers the notion of boundaries a useful, albeit wide and elusive, concept. However, recent sociological and organizational research has sharpened the concept of boundaries to enable further examination of relational processes. In this paper, we draw on this research to advance our understanding of the process of constructing boundaries in auditing. In doing so, we focus on the unique institutional conditions in Spain during the period 1850–1988. This period witnessed the overwhelming role of the State in any sphere of economic and social life. In the case of auditing, the influence of the State was augmented as the academic background became the site of influence, which resulted in educational reforms setting professional boundaries. Our findings provide some additional insights into the boundaries construction process and the dynamics of the symbolic and social boundaries contingent on the wider contexts of the audit function.